Methodologies to enhance innovation competencies in social work education. - Cavalcante, M. Tereza Leal; Jiménez, Paco López; Navarro-Segura, Lisette (Social Work Education, 2021)
Social workers are constantly called on to respond to social demands arising from new social realities. Innovation competencies are critical for social workers, and various training programmes adopt methodologies aimed at preparing future social workers to innovate and design a sustainable future for social work practice. The objective of this paper is to present some tested teaching and learning methodologies in order to promote and enhance critical social innovation competencies among social work students. Different techniques encourage the development of innovative ideas for social intervention, some of them offering experimental experiences in which students approach the innovation process through 'inspiration', 'ideation' and 'implementation'. Students identify challenges and opportunities that motivate the search for solutions. They build and share visions, test ideas and plan actions to take social innovations into real life. These methodologies have been tested and assessed, and are replicable in different social work education contexts. The results of their application are discussed in terms of the acquisition of the expected innovation competencies.